Unifying concept for the coupling between ion pumping and ATP hydrolysis or synthesis. - Hammes, G G (1982)
A mechanism is proposed for the coupling between ion transport and enzyme catalysis. The basic concept is that enzymes associated with transport exist in two possible conformations. Each conformation has the potential of catalyzing the enzymatic reaction, and pumping is associated with the conversion of one conformational form to the other. The conformational transition is triggered by the kinetic blockage of specific mechanistic steps for each conformation. Such blockages can cause a cycling between the two conformations concomitant with catalysis. This mechanistic concept is consistent with a variety of results obtained with the Na+,K+-ATPase, the Ca2+,Mg2+-ATPase, and ATP synthesizing enzymes (coupling factors).